Preclinical Assessment of Inflammatory Pain. (10th December 2015) - Muley, Milind M.; Krustev, Eugene; McDougall, Jason J.
Summary: While acute inflammation is a natural physiological response to tissue injury or infection, chronic inflammation is maladaptive and engenders a considerable amount of adverse pain. The chemical mediators responsible for tissue inflammation act on nociceptive nerve endings to lower neuronal excitation threshold and sensitize afferent firing rate leading to the development of allodynia and hyperalgesia, respectively. Animal models have aided in our understanding of the pathophysiological mechanisms responsible for the generation of chronic inflammatory pain and allowed us to identify and validate numerous analgesic drug candidates. Here we review some of the commonly used models of skin, joint, and gut inflammatory pain along with their relative benefits and limitations. In addition, we describe and discuss several behavioral and electrophysiological approaches used to assess the inflammatory pain in these preclinical models. Despite significant advances having been made in this area, a gap still exists between fundamental research and the implementation of these findings into a clinical setting. As such we need to characterize inherent pathophysiological pathways and develop new endpoints in these animal models to improve their predictive value of human inflammatory diseases in order to design safer and more effective analgesics.